Young lungs cared enough? India's frontiers in diagnosing pediatric TB - Thomas, Silla Varghese; Rajendran, Priya; Shanmugam, Sivakumar (Frontiers in Pediatrics, 2025)
This review provides an insight into pediatric tuberculosis (TB) diagnosis in India. Significant challenges still exist in the accurate diagnosis of pediatric TB due to the paucibacillary status of the bacilli and the nonspecific clinical symptoms. Despite advancements in newer diagnostics that allow for rapid identification of TB and detection of drug resistance in children, their sensitivity is compromised due to these challenges. It is crucial to consider that children may not always expectorate sputum, further complicating the diagnostic process. Testing multiple samples, like aspirates, bronchoalveolar lavages, stool, urine, saliva, and swabs, may improve sensitivity. However, the efficacy of using these samples for pediatric TB diagnosis requires extensive research to validate their accuracy and reliability. This is crucial, especially in countries like India, which bears a high burden of TB cases, making the need for novel diagnostic approaches even more pressing. This need for innovative diagnostic approaches is particularly important in countries like India, which bears a high burden of TB cases. Collaborative efforts between researchers, healthcare providers, and policymakers are essential to drive innovation and progress toward achieving the END-TB goal. In this review, we have included studies and case reports published over a decade by utilizing scientific databases like PubMed, Scopus, and Google Scholar, and a set of key search terms including “pediatric TB in India”, and “pediatric TB diagnosis”.